2017
DOI: 10.9734/jamb/2017/33879
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics Susceptibility Patterns and Plasmid Profile of Staphylococcus aureus Isolated from Patients with Wound Infections Attending Four Hospitals in Akure, Ondo State

Abstract: Aims: Several studies have documented Staphylococcus aureus as a leading pathogen implicated in wound infections with a remarkable potential for antibiotics resistance. This study determined the susceptibility patterns of S. aureus isolated from wound infections to conventional antibiotics and assessed the plasmid profile of selected multidrug resistant isolates. Study Design: This study was designed to determine the antibiotics susceptibility patterns of Staphylococcus aureus isolates from wound infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Legend: Aug= augmentin, Gen= gentamicin, Cot= cotrimoxazole, Nit= nitrofurantoin, Cro= Ceftriaxone The presence of multiple plasmids observed in some of the isolates in this study could probably be responsible for the resistance observed. Plasmids have been shown to carry genes for antibiotics resistance, a single plasmid can carry genes for resistance to multiple antibiotics [24]. This is in coherence with the work of [16] who also reported multiple plasmids in E. coli O157 isolates from water and fecal samples.…”
Section: Fig 3 Mean Diameter Of Zones Of Inhibition (Mm) Of Commercsupporting
confidence: 73%
“…Legend: Aug= augmentin, Gen= gentamicin, Cot= cotrimoxazole, Nit= nitrofurantoin, Cro= Ceftriaxone The presence of multiple plasmids observed in some of the isolates in this study could probably be responsible for the resistance observed. Plasmids have been shown to carry genes for antibiotics resistance, a single plasmid can carry genes for resistance to multiple antibiotics [24]. This is in coherence with the work of [16] who also reported multiple plasmids in E. coli O157 isolates from water and fecal samples.…”
Section: Fig 3 Mean Diameter Of Zones Of Inhibition (Mm) Of Commercsupporting
confidence: 73%
“…Last, the distinct structural environment of H. francisci's dermal denticles, characterized by pronounced riblets and troughs, may be less hospitable to Staphylococcus, despite the potential assistance provided by mucus produced from a more exposed epidermal environment. Studies outline Staphylococcus species, such as S. aureus, to be considered common primary pathogens and implicated in wound infections [48][49][50] .…”
Section: Discussionmentioning
confidence: 99%
“…The distinct, well-isolated colonies were then studied for their cultural and morphological characteristics. Gram staining and biochemical tests were conducted to confirm the identification of the isolates [11].…”
Section: Isolation and Identification Methodsmentioning
confidence: 99%